Transfusion of blood products in off-pump coronary artery bypass and conventional coronary artery revascularization. A prospective randomized study - Walczak, Maciej; Urbanowicz, Tomasz Kamil; Tomczyk, Jadwiga; Camacho, Estillita; Ligowski, Marcin; Stefaniak, Sebastian; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : There has been a growing interest in off-pump coronary artery bypass (OPCAB) grafting in recent years. Beating-heart surgery is believed to be less invasive as it allows the side effects of extracorporeal circulation to be avoided. The aim of the study was to compare blood product transfusion rates between two groups of patients undergoing surgery for ischemic heart disease with either the off-pump technique or using cardiopulmonary bypass (CPB). Material and methods: There were 152 patients enrolled in the prospective randomized study. All procedures were elective. There were 84 patients (62 men and 20 women) at the mean age of 63.74 ± 7 years who underwent OPCAB (group I), and 68 patients (54 men and 14 women) at the mean age of 63.51 ± 6 years who underwent cardiopulmonary bypass (group II). Results: There were no perioperative deaths. The mean number of grafts was 2.27 ± 0.3 (OPCAB group) and 2.63 ± 0.6 (CPB group) (p < 0.05). The mean number of packed red blood cells transfused in the OPCAB group was 2.31 ± 0.18 units/patient and 3.94 ± 0.30 units/patient in the CPB group (p < 0.05). The mean number of fresh frozen plasma units transfused was 1.13 ± 0.13 in the OPCAB group vs. 1.57 ± 0.15 in the CPB group (p < 0.05). There were 12 patients (14%) in the OPCAB group who had no transfusion. Conclusions : One of the most important advantages of the OPCAB technique is that it makes it possible to reduce the rate of blood product transfusions.